A Study of Accountant Required Skills to Have Efficient Participation in the Implementation of XBRL - Asadizeidabadi, Heshmatolah (Bina Nusantara University, 2012)
The role of the accountants in a business environment has been evolving over the years. Accountants need to have the implementation and maintenance skills of XBRL (extensible business reporting language) which is revolutionizing business reporting around the world, in the organization.Â The present study encompasses two aspects. First, it addresses the role of the accountant during the implementation and maintenance phase. Second, it finds the characteristics and skills of accountants that can help them in a successful implementation and maintenance of XBRL. In order to collect the data a questionnaire has been used. To analyze data two statistical methods, Regression and Pearson correlation have been used. The results of the study confirm that there is a significant relationship between the participation of accountants and successful implementation of XBRL.